A non-chemically selective top-down approach towards the preparation of hierarchical TS-1 zeolites with improved oxidative desulfurization catalytic performance. Issue 17 (5th February 2016) - Du, Shuting; Chen, Xiaoxin; Sun, Qiming; Wang, Ning; Jia, Mingjun; Valtchev, Valentin; Yu, Jihong
Abstract : Hierarchical TS-1 zeolites with enhanced performance in oxidative desulfurization of bulky molecules are prepared by treatment in fluoride medium. Abstract : Hierarchical TS-1 zeolites with secondary macropores have been successfully prepared by using two different fluoride-containing chemical etching post-treated routes. Hierarchical TS-1 zeolites exhibited a chemical composition similar to that of the parent material and showed remarkably enhanced catalytic activity in oxidative desulfurization reaction.